2020
DOI: 10.4102/sajr.v24i1.1887
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of oculomotor nerve palsy after endovascular management of posterior communicating artery aneurysms

Abstract: Background: Oculomotor nerve palsy (ONP) is a common clinical presentation of posterior communicating artery (PcomA) aneurysms. It remains unclear if patients have a better rate of recovery after surgical clipping or endovascular coiling.Objectives: The main objectives of this study were to assess the overall rate of ONP recovery after endovascular coiling of PcomA aneurysms, as well as to determine the associated predictive factors of oculomotor nerve recovery.Method: We retrospectively evaluated the demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The patient experienced complete resolution of the clinical symptoms after endovascular treatment, an occurrence reported in 88.3% of patients. 13 The main limitation of our experience is related to the reporting of a single, highly unusual case, with the difficulty of inferring general, therapeutic, or management considerations about this clinical issue.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The patient experienced complete resolution of the clinical symptoms after endovascular treatment, an occurrence reported in 88.3% of patients. 13 The main limitation of our experience is related to the reporting of a single, highly unusual case, with the difficulty of inferring general, therapeutic, or management considerations about this clinical issue.…”
Section: Discussionmentioning
confidence: 95%
“…The patient experienced complete resolution of the clinical symptoms after endovascular treatment, an occurrence reported in 88.3% of patients. 13 …”
Section: Discussionmentioning
confidence: 99%
“…The aneurysmal direction might affect the occurrence and recovery of ONP anatomically. Abdurahman et al reported that the non-posterolateral direction of the aneurysm showed a tendency towards better recovery compared to the posterolateral projection [ 25 ], while in another study there was no correlation between aneurysmal direction and ONP recovery [ 26 ]. In our study, posterior-lateral-inferior direction of aneurysm dome showed a tendency towards unpleasant ONP recovery compared to other directions in univariate analysis, however, there was no significant difference in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%